Evaluation of Ki-67 expression and large cell content as prognostic markers in MZL: a multicenter cohort study - Natalie S. Grover; Kaitlin Annunzio; Marcus Watkins; Pallawi Torka; Reem Karmali; Andrea Anampa-Guzmán; Timothy S. Oh; Heather Reves; Montreh Tavakkoli; Emily Hansinger; Beth Christian; Colin Thomas; et al. (Blood Cancer Journal)
Abstract Marginal zone lymphoma (MZL) can have varied presentations and pathologic features, including high Ki-67 expression ( > 20%) as well as increased numbers of large B cells (LC). However, there are limited data available demonstrating the prognostic significance of these variables in patients with MZL. In this multi-institutional retrospective cohort study of patients with MZL treated at 10 centers, we evaluated the association between the presence of Ki-67 expression and increased LCs on survival and risk of histologic transformation (HT). A total of 785 patients were included (60% with extranodal MZL, 20% with nodal MZL, and 20% with splenic MZL). Among the 440 patients with Ki-67 staining, 22% had high Ki-67 (Ki-67 >20%). The median progression-free survival (PFS) for patients with high Ki-67 was 5.4 years compared to 7.0 years for patients with low Ki-67 (HR = 1.45, 95%CI = 1.03–2.05). Ki-67 > 20% strongly correlated with high LDH level. The risk of HT was higher in patients with increased Ki-67 than those without (5-year risk, 9.8% vs 3.87%, p = 0.01). Twelve percent of patients had LC reported on biopsy with 6% having >10% LC. The presence of LC was associated with high Ki-67 (p < 0.001), but not associated with shorter PFS or overall survival (OS). The cumulative risk for HT was higher in patients with LC compared to those without LC (5-year risk, 9.4% vs 2.9%, p = 0.04). Receipt of anthracycline-based therapy did not impact PFS or OS in either group. Ki-67 staining >20% was a prognostic factor for worse survival and strongly correlated with elevated LDH. Novel therapies should be investigated for their potential ability to overcome the high-risk features in MZL. Our data reinforce the importance of obtaining biopsies at relapse or progression, particularly in patients with baseline high Ki-67 and increased LCs, given their increased risk for HT.